Comparison of different interval training methods on athletes` oxygen uptake: a systematic review with pairwise and network meta-analysis - Yang, Q.; Wang, J.; Guan, D. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Objective To (i) examine the effect size and the ranking of the training effects for the high-intensity interval training (HIIT), sprint interval training (SIT), and repeated sprint training (RST) on athletes` VO2max through network meta-analysis. (ii) investigate the effects of the training program protocols of the three methods on the improvement of VO2max through pairwise meta-analysis and meta-regression.